Assessment of job satisfaction among the senior staff nurses working at Sadar Hospital, Naogaon, Bangladesh - Morsheda, Hamima Umme; Zaman, Md Nahid Uz; Afroze, Nahid (Asian Journal of Medical and Biological Research, 2017)
This study aimed to examine nurses? job satisfaction at Sadar Hospital, Naogaon, Bangladesh. It also examines the relationships between nurses? assessment, satisfaction, attitude, and practice with respect to job satisfaction. The descriptive cross sectional study design was used to explore the job satisfaction among the staff nurses. Total number of nurses working in this hospital was 121. A total number of fifty nurses were recruited into this study in order to overcome non-response subjects. The age group 30-39 years were 40%, 40-49 years were 46% and 50+ above were 14% nurses. Male nurses were only 6% and the female were 94%. Marital status single 12%, married 80%, widow 8%. Muslim nurses were 58%, Hindu 38% and Christian 4%. Academic qualification of them was SSC 66% and H.S.C 34%. Professional qualification was Diploma in Nursing /Diploma in Midwifery 92%, B.Sc. in public Health Nursing 6% and MPH 2%. Length of service 1 to 10 years 22%, 11 to 20 years 50%, 21 to 25 years 24%, 31+ years 4%. Regarding maintaining therapeutic relationship; facing problem in duty; keeping records; receiving complicated patient; attend in duty time; maintaining aseptic techniques; maintaining work; carryout admission and discharge the results for all above questions were 100% yes. But regarding satisfy to give care 30% respondent were not satisfied; whole for job salary 68% nurses were not feel enough and remaining 32% were satisfied. Again in case of promotion to the next post most of the respondent 16% were satisfied and 84% were not satisfied. Asian J. Med. Biol. Res. December 2016, 2(4): 611-615